PENGAWETAN DUA PULUH JENIS KAYU IRIAN JAYA SECARA RENDAMAN PANAS-DINGIN - Sasa Abdurrohim; Abdurahim Martawijaya (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Twenty wood species obtained from Irion Joya measuring 5 x 5 x 60 cm were treated by hot and cold soaking using BFCA preservative with 5 and 10 percent of solution concentration. Hot immersion period was kept for 1 hour, 2 hours and 3 hours, with temperature range of 60°C-70°C, followed by cold immersion for 24 hours.The test result of the twenty wood species, after taking both penetration and retention requirements into consideration for wood uses under roof, and in the open air both without soil contact, showed that two wood species among them i.e. nifoek (Eucalyptus deglupta Bl.) and seriega (Eugenia sp.), could not be satisfactorily treated under the experimental conditions. The other eighteen species could be treated by either one, several, or all treating schedules employed in this research. Nevertheless, it is important to note that two of the eighteen species, i.e. sougwa (Palaquium multiflorum) and matoa (Pometia pinna ta Forst.) fulfilled the requirements for wood usage under the roof only without soil contact. The preservation schedule proposed for the eighteen wood species is presented in Table 4.